Students’ Perception on the Use of Spotify to Improve Students’ Pronunciation - Ilyas, Andini Amalia; Kaniadewi, Nita (Institut Agama Islam Negeri Parepare, 2023)
English is the language that predominates in the world than other language. In order to communicate on a worldwide level, especially for academic and commercial objectives. There is a need for learners to acquire communication skills. Thus, learners should have a good pronunciation. Spotify is one of the media they can choose to learn, especially to improve their Pronunciation. The objective of this research was to explore students' perception toward the use of Spotify application to improve students' pronunciation and find out which features in Spotify are the most essential in improving their pronunciation. This research used descriptive qualitative and data collected through semi-structured interviews with ten respondents. The participants from pronunciation practice class batch 2019 in university Muhammadiyah Prof. Dr. Hamka. The participants were selected using purposive sampling. The results revealed that the students agree Spotify is suitable for improving pronunciation. They explain that the features on Spotify can support their learning, especially the lyric and making playlist features. They said listening to the music and seeing the lyrics can be effective in their pronunciation and creating their own playlists can increase their interest in listening to English songs. This research was expected to give a modern application to improve pronunciation.